Dynamic Correlations and Spillovers among the East Asian Currencies - Seehapan , Nonthaporn; Sethapramote, Yuthana (Journal of Applied Economics and Management Strategy, 2024)
This paper uses the Diebold and Yilmaz (2012) spillover indices to examine the exchange rate volatility. Weekly return data from January 2002 to April 2022 from nine East Asian currencies and four major currencies are investigated to determine how the currencies are linked. The results show that the Singaporean dollar has the highest volatility spillover to (and from) other currencies. During the full sample periods, the currency spillover is coming from its own shock. The East Asian currencies were the net volatility recipients except for the Singaporean dollar and Taiwanese dollar. Moreover, during the COVID-19 pandemic period, the volatility spillover increased, which highlighted the need for policymakers to intervene to maintain currency stability. This research also includes COVID-19 factors such as the confirmed cases, deaths, vaccinations, and the government response policy to see how COVID-19 affects the exchange rate volatility. The results from the panel regression with fixed effect show that the strength of the government’s response policy and widespread vaccination rate decrease the degree of spillover in the Asian foreign exchange markets.